Pre-treatment of Single and Double Antiplatelet and Anticoagulant With Intravenous Thrombolysis for Older Adults With Acute Ischemic Stroke: The TTT-AIS Experience - Lin, Sheng-Feng; Hu, Han-Hwa; Ho, Bo-Lin; Chen, Chih-Hung; Chan, Lung; Lin, Huey-Juan; Sun, Yu; Lin, Yung-Yang; Chen, Po-Lin; Lin, Shinn-Kuang; Wei, Cheng-Yu; Lin, Yu-Te; et al. (Frontiers in Neurology, 2021)
Background: This study aimed to investigate the safety and efficacy of single antiplatelet, anticoagulant and Dual Antiplatelet pretreatment (DAPP) in older, moderate to high severity acute ischemic stroke patients treated with intravenous thrombolysis (IVT). Methods: A prospective cohort study was conducted to monitor the development of symptomatic intracranial hemorrhage (SICH) and functional outcomes at 90 days. Two different dosages of alteplase were used for IVT. Logistic regression models were used for analysis of the safety and efficacy outcomes. Results: A total of 1156 patients were enrolled and categorized into six groups based on their pretreatment medications: (1) aspirin (n = 213), (2) clopidogrel (n = 37), (3) DAPP of aspirin + clopidogrel (n= 27), (4) warfarin (n = 44), (5) any of the above pre-medications (n = 331), and (6) none of these medications as controls (n = 825). The DAPP group showed significantly increased SICH by the NINDS (adjusted OR: 4.90, 95% CI 1.28–18.69) and the ECASS II (adjusted OR: 5.09, 95% CI: 1.01–25.68) standards. The aspirin group was found to significantly improve the favorable functional outcome of the modified Rankin Scale (mRS) of 0–1 (adjusted OR: 1.91, 95% CI, 1.31.2.78), but no significance for mRS of 0–2 (adjusted OR: 1.39, 95% CI, 0.97–1.99). The DAPP group also significantly increased mortality (adjusted OR: 4.75, 95% CI: 1.77–12.72). A significant interaction between different dosages for IVT and the functional status was noted. Compared to standard dose, the DAPP group showed higher proportions of disability and mortality with low dose of IVT. Conclusion: For older adults with higher baseline severity of acute ischemic stroke, DAPP may increase the risk of SICH and mortality post IVT. However, DAPP is still not an indication to withdraw IVT and to prescribe low-dose IVT for older adults.